Strategi Membangun Budaya Organisasi yang Inovatif dalam Menghadapi Era Digital - Manurung, Febriani; Hasibuan, Wildan Anshori; Ananda, Fauzi; Nisa, Mahmudan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze effective strategies for building an innovative organizational culture to face challenges in the digital era. The research method used is a qualitative study with a case study approach in technology companies in Indonesia. Data were collected through in-depth interviews and company document analysis. The results show that the implementation of transformational leadership, technology-based human resource development, and the creation of a collaborative work environment are key strategies in fostering an innovative culture. These findings are expected to serve as a reference for companies in adapting to digital developments.